2022
DOI: 10.3390/ijms23073733
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis as a Novel Facet of Mitotic Catastrophe

Abstract: Mitotic catastrophe is a defensive mechanism that promotes elimination of cells with aberrant mitosis by triggering the cell-death pathways and/or cellular senescence. Nowadays, it is known that apoptosis, autophagic cell death, and necrosis could be consequences of mitotic catastrophe. Here, we demonstrate the ability of a DNA-damaging agent, doxorubicin, at 600 nM concentration to stimulate mitotic catastrophe. We observe that the inhibition of caspase activity leads to accumulation of cells with mitotic cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Apoptosis is highly regulated and is characterized by membrane blebbing, cell shrinkage, and caspase activation. Necroptosis, a more recently characterized form, is triggered by various factors, including caspase inhibition or impairment ( Egorshina et al, 2022 ; Sahoo et al, 2023 ). Necroptosis relies on RIPK1 and RIPK3 activation, and its morphology differs from apoptosis with organelle swelling and membrane rupture ( Vandenabeele et al, 2010 ; Shan et al, 2018 ; Bertheloot et al, 2021 ).…”
Section: Trif-dependent Tlr3 Signalingmentioning
confidence: 99%
“…Apoptosis is highly regulated and is characterized by membrane blebbing, cell shrinkage, and caspase activation. Necroptosis, a more recently characterized form, is triggered by various factors, including caspase inhibition or impairment ( Egorshina et al, 2022 ; Sahoo et al, 2023 ). Necroptosis relies on RIPK1 and RIPK3 activation, and its morphology differs from apoptosis with organelle swelling and membrane rupture ( Vandenabeele et al, 2010 ; Shan et al, 2018 ; Bertheloot et al, 2021 ).…”
Section: Trif-dependent Tlr3 Signalingmentioning
confidence: 99%
“…Mitotic catastrophe is another critical non-apoptotic mechanism of cancer cells, defined by the Nomenclature Committee on Cell Death (NCCD) in 2012, which usually occurs after massive damage to DNA following ROS generation ( Galluzzi et al, 2012 ). Cells undergoing mitotic catastrophe are often in partnership with other mechanisms of cell death, such as autophagy, senescence, or, necroptosis ( Eom et al, 2005 ; Zhao W. et al, 2022b ; Egorshina et al, 2022 ). Recent studies have found that the therapeutic efficiency of anticancer modalities such as radiotherapy and chemotherapy can be reinforced by stimulating mitotic catastrophe, which is also a promising way to overcome multidrug resistance ( Pérès et al, 2015 ; Bai et al, 2017 ).…”
Section: Therapeutic Mechanisms Of Quercetin Targeting Non-apoptotic ...mentioning
confidence: 99%
“…When TNF interacts with TNFR1, the intracellular part of TNFR1 binds with the adaptor protein TRADD. This event leads to the assembly of an intracellular complex, which includes caspases and serine protein kinases RIP1 and RIP3 [20,21]. Depending on the activation of these enzymes, alternative processes of cell death are induced in the cells: apoptosis and necroptosis [22,23].…”
Section: Introductionmentioning
confidence: 99%